Elevated Anxiety and Impaired Attention in Super-Smeller, Kv1.3 Knockout Mice - Huang, Zhenbo; Hoffman, Carlie A.; Chelette, Brandon M.; Thiebaud, Nicolas; Fadool, Debra A. (Frontiers in Behavioral Neuroscience, 2018)
It has long been recognized that olfaction and emotion are linked. While chemosensory research using both human and rodent models have indicated a change in emotion can contribute to olfactory dysfunction, there are few studies addressing the contribution of olfaction to a modulation in in emotion. In mice, olfactory deficits have been linked with heightened anxiety levels, suggesting that there could be an inverse relationship between olfaction and anxiety. Furthermore, increased anxiety is often co-morbid with psychiatric conditions such as attention disorders. Our study aimed to investigate the roles of olfaction in modulating anxiety. Voltage-gated potassium ion channel Kv1.3 knockout mice (Kv1.3-/-), which have heightened olfaction, and wild-type (WT) mice were examined for anxiety-like behaviors using marble burying, light-dark box, and elevated-plus maze tests. Because Kv1.3-/- mice have increased locomotor activity, inattentive and hyperactive behaviors were quantified for both genotypes. Kv1.3-/- mice showed increased anxiety levels compared to their WT counterparts and administration of methylphenidate (MPH) via oral gavage alleviated their increased anxiety. Object-based attention testing indicated young and older Kv1.3-/- mice had attention deficits and treatment with MPH also ameliorated this condition. Locomotor testing through use of a metabolic chamber indicated that Kv1.3-/- mice were not significantly hyperactive and MPH treatment failed to modify this activity. Our data suggest that heightened olfaction does not necessarily lead to decreased anxiety levels, and that Kv1.3-/- mice may have behaviors associated with inattentiveness.